An Analysis Of Ellipsis In Are You There, God? It’s Me, Margaret Script - Rosa Ikaputri, Carmelia; Artawa, Ketut (Peneliti.net, 2026)
This study examines the utilization of ellipsis in the dialogues of the film Are You There God? It’s Me, Margaret. This study concentrates on the varieties of ellipsis and the importance of its use in daily conversation as illustrated by the film. The objective of this research is to demonstrate the manner in which ellipsis reflects the patterns of ordinary conversation, emphasizing its significance in the development of shared understanding and social connections. The research enhances the understanding of ellipsis as a critical component of grammatical cohesion in cinematic narratives. The film's dialogues were documented and analyzed using a qualitative methodology for data acquisition. In order to categorize the film according to the applicable theory, it was viewed on numerous occasions. The ellipsis theory, as proposed by Halliday and Hasan, is employed in this investigation to classify ellipsis into three primary categories: nominal, verbal, and clausal. The results indicate that ellipsis is not only used to improve grammatical cohesion but also to facilitate effective communication among characters.